PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS SCRATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA INSTITUT PENDIDIKAN TAPANULI SELATAN - Lubis, Roslian; Harahap, Muhammad Syahril; Khomeni, Ayatollah; Hasibuan, Hamzah (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to develop a Scratch-based mathematics learning media on the topic of rings (Gelanggang) to enhance the learning motivation of students at the Institute of Education Tapanuli Selatan. The research employed a Research and Development (R&D) method using the 4D development model, which includes Define, Design, Develop, and Disseminate stages. The research subjects were two fourth-semester students from the mathematics education program at the Institute of Education Tapanuli Selatan. Data were collected through observation, interviews, questionnaires, and documentation. The validity of the media was evaluated by experts in content, media, and language, while practicality and effectiveness were assessed using student response questionnaires and learning outcome tests. The validation results indicated that the Scratch-based mathematics learning media was in the "Highly Valid" category, with an average validation score of 94%. The practicality test showed that the media was categorized as "Highly Practical," and the effectiveness test revealed a significant increase in students' learning motivation. Therefore, the developed Scratch-based mathematics learning media is effective in enhancing learning motivation and can be used as an innovative alternative learning medium in higher education environments.